2018
DOI: 10.1099/ijsem.0.002970
|View full text |Cite
|
Sign up to set email alerts
|

Haloplanus rallus sp. nov., a halophilic archaeon isolated from crude solar salt

Abstract: A halophilic archaeon, strain MBLA0036, was isolated from Sorae solar saltern near Incheon, Republic of Korea. Strain MBLA0036 had three 16S rRNA genes: rrnA, rrnB and rrnC. The 16S rRNA gene sequence similarities between strain MBLA0036 (based on the rrnA gene) and Haloplanus ruber R35 and Haloplanus litoreus GX21 were 98.0 and 97.3 %, respectively. The similarities of the RNA polymerase subunit B' gene between strain MBLA0036 and H. ruber R35 and H. litoreus GX21 were 94.0 and 92.1 %, respectively. Cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…in metabolic product (Cho et al, 2018). These findings suggested that sulfur metabolism may be coupled with carbon metabolism in mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 80%
“…in metabolic product (Cho et al, 2018). These findings suggested that sulfur metabolism may be coupled with carbon metabolism in mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 80%
“…Magnesium sulfat (MgSO4) atau yang sering disebut dengan garam Inggris yang dapat dijumpai dalam bentuk magnesium sulfat heptahidrat (MgSO4.7H2O) merupakan salah satu produk industri. MgSO4.7H2O atau magnesium sulfat heptahidrat sering dinamakan dengan garam Epsom (91)(92)(93)(94)(95) .…”
Section: Pendahuluanunclassified
“…Magnesium sulfat (MgSO4) atau yang sering disebut dengan garam Inggris yang dapat dijumpai dalam bentuk magnesium sulfat heptahidrat (MgSO4.7H2O) merupakan salah satu produk industri. MgSO4.7H2O atau magnesium sulfat heptahidrat sering dinamakan dengan garam Epsom (91)(92)(93)(94)(95) .Magnesium sulfat memiliki nilai pH sekitar 6,0 (5,5 -6,5) pada keadaan standar dan tekanan uap pada suhu 20°C < 0,01 mmHg (96)(97)(98) . Magnesium sulfat anhidrat (99-103) bersifat sangat higroskopik oleh karenanya senyawa magnesium sulfat biasa didapati dalam bentuk hidrat dengan struktur kristal monoklin.…”
unclassified
“…2017; Cho et al . 2018) have been well documented. Micro‐organisms such as Bacteria (Salinibacter), Eucarya ( Dunaliella salina ) and red halophilic Archaea adapt to life in high‐salinity water such as the crystallization ponds (Ma et al .…”
Section: Introductionmentioning
confidence: 99%
“…The role of halophilic organisms, that is, Archaean, has been reported in several salt systems across the globe (Oh et al 2010;Carpa et al 2014;Deng et al 2015;Plominsky et al 2018;G omez-Villegas et al 2018). Many other studies of saline environments inhabitants, such as in salt lakes (Oren et al 1995;Yang et al 2007;Hedi et al 2009;Najjari et al 2015;Naghoni et al 2017; Barreteau et al 2019), and commercial salt both from rock salt as well as salt from seawater (Gibtan et al 2017;Cho et al 2018) have been well documented. Micro-organisms such as Bacteria (Salinibacter), Eucarya (Dunaliella salina) and red halophilic Archaea adapt to life in high-salinity water such as the crystallization ponds (Ma et al 2010).…”
Section: Introductionmentioning
confidence: 99%